Competência leitora: uma proposta interdisciplinar - Santos, Laura Lúcia de Oliveira (2015)
Over the recent years, the discussion about what is read and the school's role in the player's training emphasized in education reflections. The documents that guide the public education of São Paulo, since 2008, put this issue as one of its pillars: treat by priority to reading competence and to extend to the writer. The theme of this work is the competence reader. We describe the proposals of the State of São Paulo for the treatment of reading in Portuguese, Geography and History in a school State Network, located 180 kilometers from the capital. Here is thus a public school context in São Paulo, classified as unsatisfactory condition regarding the proficiency scale defined in public documents and within the limits of this study, we aimed to determine which reading on impressions are known by teachers of the humanities. We seek to relate understanding of reading and strategies that the subjects use on a daily basis in order to relate them to the data of the external evaluations. Then we draw a brief historical background on the subject and carry on about the importance of reading in sociointeracional understood aspect of the development of students. We work on Fischer (2006), Solé (1998), and Kleiman (2002). We emphasize teacher training as a precondition for performing a job that contributes to the development of reading competence. Finally, we present a proposal for interdisciplinary work from a song, you want to get involved in the formation of readers teachers of Portuguese Language, History and Geography. We emphasize the selection of strategies to develop the skills necessary readers for the proper formation of the student and their integration into society. We take care to shed light on a reflection on the reading, with the intention to rethink their teaching and practice